1978
DOI: 10.1007/bf01323461
|View full text |Cite
|
Sign up to set email alerts
|

Studies on blood-brain barrier permeability after microwave-radiation

Abstract: Since the reported alterations of permeability of the blood-brain barrier by microwave radiation have implications for safety considerations in man, studies were conducted to replicate some of the initial investigations. No transfer of parenterally-administered fluorescein across the blood-brain barrier of rats after 30 min of 1.2-GHz radiation at power densities from 2--75 mW/cm2 was noted. Increased fluorescein uptake was seen only when the rats were made hyperthermic in a warm-air environment. Similarly, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
41
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(41 citation statements)
references
References 6 publications
(13 reference statements)
0
41
0
Order By: Relevance
“…Merritt (1977) endeavored to repeat the experiments of Oscar and Hawkins, but did not obtain sliiii.lar results. Data from three of his experiments indicated that hypertherrnia of the brain is necessary to alter prrneabi1ity.…”
Section: -31mentioning
confidence: 99%
“…Merritt (1977) endeavored to repeat the experiments of Oscar and Hawkins, but did not obtain sliiii.lar results. Data from three of his experiments indicated that hypertherrnia of the brain is necessary to alter prrneabi1ity.…”
Section: -31mentioning
confidence: 99%
“…Both of these groups used anesthetized animals. Frey et al (1975) claimed to see alterations of BBB permeability to NaFl under 0 certain RFR-exposure conditions, but their results could not be confirmed by Merritt et al (1978),…”
mentioning
confidence: 95%
“…The authors noted that Oscar and Hawkins (1977), who used the brainuptake-index (BUI) technique of Oldendorf (1970), had reported that BBB permeability to mannitol and inulin in the rat could be increased by exposure to 1.3-GHz CW or pulsed RFR at an average power density of 3 mW/sq cm, that attempts by Merritt et al (1978) to replicate these results using identical exposure parameters and conditions were unsuccessful, and that in another attempt with 2.45-GHz RFR, Preston et al (1979) were unable to obtain significant changes in cerebral permeability to mannitol. They also noted that Oscar et al (1981), using the in-vivo C-14-iodoantipyrine technique, had obtained increased cerebral blood flow from RFR exposure, which could affect BUI estimates of BBB permeability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An Oldendorf [1970] double isotope procedure for studying blood-brain barrier was also used by Merritt et al [1978]. Four different 1. were not used.…”
mentioning
confidence: 99%